Kajian Lafaz Muthlaq dan Muqayyad Ditinjau dari Cakupan Makna, Penerapan dalam Nash, dan Implikasi Hukumnya - Abdul Aziz Anwar; Abdul Syatar; Fatmawati F (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Al-Qur'an is a holy book that is a guide for all mankind in living life on earth. The Qur'an is a book with extraordinary privileges and secrets, not least when viewed in terms of its pronunciation, such as the issue of muthlaq and muqayyad. This study discusses the concept of muthlaq and muqayyad expressions in Islamic legal theory (ushul fiqh) from the perspective of the scope of meaning and their influence on legal interpretation. The objective of this research is to analyze the meaning of muthlaq and muqayyad, examine their application in the Qur’an and Hadith. This research employs a qualitative method through library research by examining classical and contemporary literature of ushul fiqh. The study finds that muthlaq refers to a text with unrestricted meaning, while muqayyad refers to a text limited by certain attributes or conditions. In legal interpretation, scholars often apply the principle of haml al-muthlaq ‘ala al-muqayyad to harmonize legal texts and avoid contradictions. The understanding of these two forms of expressions significantly affects legal rulings and contributes to differences of opinion among Islamic jurists. Therefore, the study of muthlaq and muqayyad remains essential in understanding Islamic legal methodology and addressing contemporary legal issues.